Relationship between structural remodeling and the high risk of recurrence in auricular fibrillation - Annalie Fidelina Rondón-Vázquez (Universidad Médica Pinareña, 2020)
Introduction: atrial fibrillation is a supraventricular tachycardia characterized by disorganized, uncoordinated atrial activation, with negative consequences on atrial mechanical function.